Impact of pharmacist intervention to deprescribe inappropriate aspirin therapy in an outpatient anticoagulation clinic at a community hospital - Brooke J. Domaleczny; Susan J. Lewis; Jennifer L. Richardson; Heather R. Eid (American Heart Journal Plus, 2022)
Study objective: This study describes a pharmacist-led process to identify and discontinue inappropriate aspirin in patients receiving concomitant anticoagulant therapy and to evaluate the effectiveness of the intervention. Setting: The study took place in an outpatient anticoagulation clinic within a small community hospital. Participants: Patients ≥40 years old on indefinite anticoagulation therapy for atrial fibrillation and/or venous thromboembolism were included. Design: This is a quality improvement initiative. Interventions: Utilizing the electronic medical record and patient interview, use and indication for daily aspirin therapy was confirmed. Prospectively collected patient demographics and past medical history were used to determine appropriateness of aspirin therapy. For patients identified as receiving inappropriate aspirin therapy, a fax was sent to the referring provider recommending aspirin discontinuation. Main outcome measures: To assess the effectiveness of the intervention, outcomes were retrospectively measured. The primary outcome was the percentage of “accepted” recommendations. Secondary outcomes included the prevalence, dosing, and indications for aspirin therapy. Results: Eighty (33 %) of 242 patients were on aspirin. Fifty-two patients with atrial fibrillation and/or venous thromboembolism were assessed and aspirin was deemed inappropriate in 22 patients. The provider agreed with deprescribing aspirin therapy in 45 %. The most common dose and indication of aspirin therapy was 81 mg (98 %) and primary prevention (40 %) respectively. Conclusions: In our small practice, pharmacist-led interventions were an effective means to recommend aspirin discontinuation in our identified patients. Further studies are needed to optimize a pharmacist's role and address the long-term effects of deprescription.